If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(p-1)(2p-3)=0
We multiply parentheses ..
(+2p^2-3p-2p+3)=0
We get rid of parentheses
2p^2-3p-2p+3=0
We add all the numbers together, and all the variables
2p^2-5p+3=0
a = 2; b = -5; c = +3;
Δ = b2-4ac
Δ = -52-4·2·3
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1}=1$$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-1}{2*2}=\frac{4}{4} =1 $$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+1}{2*2}=\frac{6}{4} =1+1/2 $
| 25x^2-4x+16=0 | | 8x^2-49x-49=0 | | (3y+2)+3y=127 | | .5a+6.2=12 | | (x+7)(8x+-7)=0 | | 4=2^x | | -16*t^2+14t+12=0 | | 6x+4+8x-16=180 | | 2(4t-6)=21t+7 | | -15=x-81= | | 3(2x-5)=2(3x-1)+1x | | 16t^2-50t+27=0 | | 3x−2.4=9.6, | | 2(4t-6)=19t+8 | | 3+2(x+4)=4x-1 | | x-4-3x=6x=x=25 | | 4(x-2)^2=64 | | 2(x-3)-3=5x-3(4+x) | | 3w^+7w=6 | | x2+6x+10=37 | | 2x(4x+-1)=4+2x | | -5v+3=-37 | | 4=2.3^x | | -8-2q=-16 | | 4x+x-5=11x-5x+7 | | x+.35x=30.18 | | -5z-8=-18 | | -3d-1=-13 | | (x/3.9)=(6/11) | | 6-5n=-24 | | 256^x=4 | | 8^x-7=3 |